Pseudoprogression as a prognostic biomarker in glioblastoma patients - Juliana Maria da Cruz Pinto Teixeira (2022)
Background: Pseudoprogression (PsP) has been reported as a predictor of a better prognosis in glioblastoma patients. However, other authors have failed to observe an improvement in overall survival (OS) in PsP patients. Thereby, we aimed to investigate the prognostic significance of PsP in glioblastoma patients, by assessing OS and progression-free survival (PFS). Methods: We performed a retrospective analysis on newly diagnosed glioblastoma patients from January 2014 to December 2018. Considering imaging features on follow-up MRI scans at six months, subjects were categorized by the diagnosis of progressive disease (PD) or non-progressive disease (nPD). Further, we conducted a sub-group analysis within the nPD patients, based on PsP presence (PsP vs. n-PsP subgroups). Survival analysis was performed employing the Kaplan-Meier method. Results: Of the 129 patients included, 63 (48.8%) patients were classified as PD and 66 (51.2%) as nPD. Mean OS for PD and nPD were 11.59 and 24.43 months, respectively (p<0.01). Mean PFS for PD was 4.03 months and for nPD was 12.69 months (p<0.01). As for the subgroup analysis, PsP was found in 8 cases among the nPD cohort (12.1%). Mean OS for PsP and n-PsP were 24.36 and 22.17 months, respectively (p=0.732). Mean PFS for PsP was 18.92 months and for n-PsP was 11.78 months (p=0.0265). In multivariate analysis, PsP is not correlated with higher OS (Coeff. 1.30, p=0.806) or PFS (Coeff. 5.44, p=0.094). Conclusion: PsP does not suggest an improved OS compared to stable disease. Therefore, our findings do not support a prognostic significance in glioblastoma patients.